2010
DOI: 10.1093/carcin/bgq046
|View full text |Cite
|
Sign up to set email alerts
|

A new conditional Apc-mutant mouse model for colorectal cancer

Abstract: Mutations of the adenomatous polyposis coli (APC) gene predispose individuals to familial adenomatous polyposis (FAP), characterized by multiple tumours in the large intestine. Most mouse models heterozygous for truncating mutant Apc alleles mimic FAP, however, the intestinal tumours occur mainly in the small intestine. To model large intestinal tumours, we generated a new conditional Apc-mutant allele, Apc(15lox), with exon 15 flanked by loxP sites. Similar survival of Apc(1638N/15lox) and Apc(1638N/+) mice i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 35 publications
(59 reference statements)
1
67
0
Order By: Relevance
“…1). 23,24 Apc is part of the socalled destruction complex and as such involved in phosphorylation of b-catenin, which marks this protein for degradation. Cre-mediated recombination of Apc destroys the degradation complex, resulting in the stabilization of bcatenin, allowing translocation to the nucleus where it displaces the transcription repressor Groucho (TLE), permitting members of the TCF/LEF transcription factor family to regulate Wnt target gene transcription.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). 23,24 Apc is part of the socalled destruction complex and as such involved in phosphorylation of b-catenin, which marks this protein for degradation. Cre-mediated recombination of Apc destroys the degradation complex, resulting in the stabilization of bcatenin, allowing translocation to the nucleus where it displaces the transcription repressor Groucho (TLE), permitting members of the TCF/LEF transcription factor family to regulate Wnt target gene transcription.…”
Section: Resultsmentioning
confidence: 99%
“…23 Apc ex15lox mice were developed at our university by Fodde and Smits. 24 Male Pgr Cre/1 mice were bred with female Apc ex15lox/lox mice to eventually obtain Pgr Cre/1 ; Apc ex15lox/lox mice. Pgr Cre/1 mice were used as controls.…”
Section: Generation Of Mice and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Somatic Apc deletion is predicted to result in the constitutive activation of the canonical Wnt pathway and, possibly, in the nuclear accumulation of β-catenin (Gaspar and Fodde, 2004;Robanus-Maandag et al, 2010). However, IHC analysis of β-catenin expression in the uterus of Amhr2 Cre/+ ;Apc 15lox/15lox animals revealed that the majority of myometrial cells are marked by cytoplasmatic β-catenin staining with only few cells showing nuclear staining (Fig.…”
Section: The Amhr2 Promoter Is Mainly Active In the Myometriummentioning
confidence: 96%
“…Amhr2Cre mice were bred with Rosa26 reporter mice (Soriano, 1999) to review Cre expression, and were bred with Apc 15lox mice (Miclea et al, 2009;Robanus-Maandag et al, 2010) to obtain Apc 15flox/15flox mice ("flox" means that the sequence between two loxP sites has been deleted by Cre). PgrCre animals (Soyal et al, 2005) …”
Section: Animals and Genotypingmentioning
confidence: 99%